High-strength hardware stamping die and preparation method thereof

By using boron-containing tungsten carbide, modified cobalt powder and nitrogen-doped chromium carbide to prepare high-strength hardware stamping molds, the problem of insufficient mold hardness and fracture strength is solved, and the comprehensive improvement of hardness and toughness is achieved.

CN120269009AInactive Publication Date: 2025-07-08DONGGUAN LONGSHENG HARDWARE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510450814.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-09
Publication Date
2025-07-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing hardware stamping molds have low Rockwell hardness, insufficient lateral fracture strength, and poor fracture toughness.

Method used

High-strength hardware stamping molds are prepared by ball milling, spray drying, dewax and sintering and quenching treatment, and the synergistic effect of each component is used to improve the hardness and breaking strength of the mold by using the synergistic effect of each component.

Benefits of technology

The Rockwell hardness and lateral fracture strength of the mold are significantly improved, while good fracture toughness is obtained, which enhances the overall performance of the mold.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of alloy dies, and particularly relates to a high-strength hardware stamping die and a preparation method thereof. Boron-containing tungsten carbide is selected as a main component of the die, modified cobalt powder and nitrogen-doped chromium carbide are used together, the high-strength hardware stamping die is prepared, through the synergistic effect of all the components, the Rockwell hardness and transverse breaking strength of the die are effectively improved, and meanwhile good breaking tenacity is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Summary of the Invention

[0001] Aiming at the deficiencies of the prior art, the purpose of the present invention is to provide a high-strength hardware stamping die and its preparation method, aiming to solve the problems of low Rockwell hardness, insufficient transverse fracture strength, and poor fracture toughness in the existing technology.

[0002] The present invention selects tungsten carbide containing boron as the main component of the die, and combines the common use of modified cobalt powder and nitrogen-doped chromium carbide to prepare a high-strength hardware stamping die. Through the synergistic effect of each component, the Rockwell hardness and transverse fracture strength of the die are effectively improved, and good fracture toughness is obtained at the same time.

[0003] The technical solutions adopted by the present invention to solve the above technical problems are as follows:

[0004] In the first aspect of the present invention, a preparation method of a high-strength hardware stamping die is provided, including the following steps:

[0005] Step S1: By weight, mix 20 - 30 parts of tungsten carbide and 40 - 50 parts of vinyl polycarbosilane evenly, then ball mill for 50 - 60 h, and then under the protection of nitrogen gas, heat up to 1000 - 1200 °C and keep warm for 60 - 90 min, and cool to room temperature to obtain a porous material; mix 20 - 30 parts of the porous material and 6 - 8 parts of boron quantum dots, under the protection of helium gas, heat up to 1600 - 1700 °C and keep warm for 1 - 3 h, cool to room temperature at a rate of 6 - 10 °C / min, and pulverize to obtain tungsten carbide containing boron;

[0006] Step S2: By weight, mix 50 - 60 parts of the tungsten carbide containing boron, 30 - 40 parts of cobalt powder, 4 - 6 parts of chromium carbide, and 2 - 4 parts of carbon black evenly, and then carry out ball milling treatment to obtain a slurry;

[0007] Step S3: Spray-dry the slurry, then press it into a green compact, and carry out dewaxing and sintering treatment on the green compact to obtain a sintered compact;

[0008] Step S4: Quench the sintered compact and then carry out low-temperature tempering treatment to obtain a high-strength hardware stamping die.

[0009] As a preferred technical solution of the present invention, the preparation method of the boron quantum dots includes: by weight, add 2 - 4 parts of boron powder to 80 - 100 parts of isopropyl alcohol and mix evenly, then add 4 - 6 parts of boric acid and 6 - 8 parts of hydrogen peroxide, and carry out ultrasonic crushing at a power of 600 - 640 W for 120 - 160 min. After the ultrasonic crushing is completed, add 3 - 5 parts of sodium borohydride and stir for 22 - 24 h, centrifuge to obtain the supernatant, add 2 - 4 parts of hydrazine hydrate to the supernatant and carry out ultrasonic oscillation for 20 - 30 min, and freeze-dry to obtain the boron quantum dots.

[0010] Boron-containing tungsten carbide contains boron quantum dots, which can act as a grain growth inhibitor of tungsten carbide during the sintering process, helping to maintain a fine grain size, thereby bringing higher hardness; at the same time, nano-level boron quantum dots are dispersed in the tungsten carbide matrix, which can effectively hinder dislocation movement, thereby improving the overall Rockwell hardness of the material.

[0011] As a preferred technical solution of the present invention, the cobalt powder is modified cobalt powder; the preparation method of the modified cobalt powder comprises: adding 20 to 30 parts of cobalt powder and 6 to 10 parts of graphene oxide to 90 to 100 parts of deionized water by weight, mixing them evenly by ball milling to obtain a mixed solution, freeze-drying the mixed solution to obtain a composite powder, and then heat-treating the composite powder under the protection of a hydrogen atmosphere (temperature of 520 to 540°C, time of 2 to 4 hours) to obtain modified cobalt powder.

[0012] Modified cobalt powder can effectively disperse stress and prevent crack propagation by introducing graphene with high Young's modulus and high strength, thereby improving the material's resistance to fracture. At the same time, the two-dimensional layer structure of graphene can provide additional support when subjected to force, increasing the transverse fracture strength of the stamping die.

[0013] As a preferred technical solution of the present invention, the chromium carbide is nitrogen-doped chromium carbide; the preparation method of the nitrogen-doped chromium carbide comprises: adding 8 to 12 parts of chromium nitrate, 1 to 3 parts of glycine and 10 to 14 parts of glucose to 40 to 50 parts of deionized water by weight, mixing evenly, then heating and stirring at 140 to 160° C. for 40 to 60 minutes, and drying to obtain a precursor powder; mixing 10 to 16 parts of the precursor powder and 6 to 8 parts of urea and placing them in a tubular furnace, performing high-temperature treatment under nitrogen atmosphere protection, cooling to room temperature after the high-temperature treatment, washing, and drying to obtain nitrogen-doped chromium carbide.

[0014] As a preferred technical solution of the present invention, the conditions of the high temperature treatment include: a temperature of 760 to 780° C. and a time of 2 to 4 hours.

[0015] The solid solution of nitrogen atoms in nitrogen-doped chromium carbide in the crystal structure can hinder the movement of dislocations, indirectly improving the material's ability to resist crack propagation. At the same time, nitrogen doping can adjust the residual stress distribution inside the material to avoid local stress concentration, thereby improving the fracture toughness of the mold.

[0016] As a preferred technical solution of the present invention, the ball milling conditions include: first adding 6 to 10 parts of paraffin wax for pre-grinding for 10 to 20 minutes, and then adding 400 to 500 parts of anhydrous ethanol for ball milling at 38 to 40 r / min for 24 to 28 hours.

[0017] As a preferred technical solution of the present invention, the conditions for the dewaxing sintering treatment include: introducing high-pressure argon gas at a temperature of 1320-1340°C, a pressure of 8-10 bar, a sintering time of 30-40 minutes, and taking out of the furnace after cooling.

[0018] As a preferred technical solution of the present invention, the conditions for the quenching treatment include: heating to 760-800°C at a heating rate of 4°C / min in a vacuum environment, keeping warm for 20-30 minutes, then heating to 1000-1100°C at a heating rate of 5°C / min, keeping warm for 30-40 minutes, and finally filling with 1-3 bar argon gas and rapidly cooling to room temperature.

[0019] As a preferred technical solution of the present invention, the conditions of the low-temperature tempering treatment include: heating to 180-200°C at a heating rate of 1°C / min, keeping warm for 4-6 hours, and naturally cooling to room temperature.

[0020] The second aspect of the present invention provides a high-strength metal stamping die prepared by the method described in the first aspect.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] (1) The stamping die of the present invention needs to be subjected to high-temperature treatment during the preparation process. High temperature will promote the migration and penetration of various atoms in the material, and the mesoporous chromium carbide in the nitrogen-doped chromium carbide can provide space for the penetration of boron quantum dots in boron-containing tungsten carbide. As part of the boron quantum dots migrate into the nitrogen-doped chromium carbide and combine with nitrogen elements under high temperature conditions to form a boron nitride phase structure, the structure can also interweave with the two-dimensional layer structure of graphene in the modified cobalt powder, thereby improving the Rockwell hardness of the die, increasing the transverse fracture strength, and ensuring good fracture toughness.

[0023] (2) The boron-containing tungsten carbide of the present invention contains boron quantum dots, which can act as a tungsten carbide grain growth inhibitor during the sintering process, helping to maintain a fine grain size, thereby bringing higher hardness; at the same time, nano-scale boron quantum dots are dispersed in the tungsten carbide matrix, which can effectively hinder dislocation movement, thereby improving the overall hardness of the material.

[0024] (3) The modified cobalt powder of the present invention can effectively disperse stress and prevent crack propagation by introducing graphene with high Young's modulus and high strength, thereby improving the material's resistance to fracture. At the same time, the two-dimensional layer structure of graphene can provide additional support when subjected to stress, thereby increasing the transverse fracture strength of the stamping die through a comprehensive effect.

[0025] (4) The solid solution of nitrogen atoms of the nitrogen-doped chromium carbide of the present invention in the crystal structure can hinder the movement of dislocations, indirectly improving the crack propagation resistance of the material. At the same time, the residual stress distribution inside the material can be adjusted by nitrogen doping to avoid local stress concentration, thereby improving the fracture toughness of the mold. Detailed implementation manners

[0026] To facilitate the understanding of the present invention, the following examples are listed. Those skilled in the art should understand that the said examples are only for helping to understand the present invention and should not be regarded as specific limitations on the present invention.

[0027] The sources of some components in the examples and comparative examples are as follows:

[0028] Tungsten carbide, CAS No. 12070-12-1, purchased from Shanghai Macklin Biochemical Co., Ltd.;

[0029] Cobalt powder, CAS No. 7440-48-4, purchased from Shanghai Macklin Biochemical Co., Ltd.;

[0030] Chromium carbide, CAS No. 12012-35-0, purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0031] Carbon black, CAS No. 1333-86-4, purchased from Nantong Runfeng Petrochemical Co., Ltd.;

[0032] Boron powder, CAS No. 7440-42-8, purchased from Shanghai Macklin Biochemical Co., Ltd.;

[0033] Isopropyl alcohol, CAS No. 67-63-0, purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0034] Boric acid, CAS No. 10043-35-3, purchased from Shanghai Macklin Biochemical Co., Ltd.;

[0035] Hydrogen peroxide, CAS No. 7722-84-1, purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0036] Sodium borohydride, CAS No. 16940-66-2, purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0037] Hydrazine hydrate, CAS No. 10217-52-4, purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0038] Vinyl polycarbosilane, model VHCPS, purchased from the Institute of Chemistry, Chinese Academy of Sciences;

[0039] Graphene oxide, product number G139803, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0040] Chromium nitrate, CAS No. 7789-02-8, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0041] Glycine, CAS No. 56-40-6, was purchased from Shanghai Macklin Biochemical Co., Ltd.;

[0042] Glucose, CAS No. 50-99-7, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0043] Urea, CAS No. 57-13-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.

[0044] Preparation of boron quantum dots: By weight, 4 parts of boron powder were added to 100 parts of isopropanol and mixed evenly, then 6 parts of boric acid and 8 parts of hydrogen peroxide were added, and ultrasonic fragmentation was carried out at a power of 600W for 160min. After the ultrasonic fragmentation was completed, 5 parts of sodium borohydride were added and stirred for 24h. The supernatant was obtained by centrifugation. 4 parts of hydrazine hydrate were added to the supernatant and ultrasonic oscillation was carried out for 30min, followed by freeze-drying to obtain the boron quantum dots.

[0045] Preparation of modified cobalt powder: By weight, 30 parts of cobalt powder and 10 parts of graphene oxide were added to 100 parts of deionized water, and ball milling was carried out to mix evenly to obtain a mixed solution. The mixed solution was freeze-dried to obtain a composite powder, and then the composite powder was heat-treated under a hydrogen atmosphere (temperature: 540°C, time: 2h) to obtain the modified cobalt powder.

[0046] Preparation of nitrogen-doped chromium carbide: By weight, 12 parts of chromium nitrate, 3 parts of glycine and 14 parts of glucose were added to 50 parts of deionized water and mixed evenly, and then heated and stirred at 160°C for 40min, and dried to obtain a precursor powder; 16 parts of the precursor powder and 8 parts of urea were mixed and placed in a tubular furnace, and high-temperature treatment was carried out under a nitrogen atmosphere (temperature: 780°C, time: 2h). After the high-temperature treatment was completed, it was cooled to room temperature, washed, and dried to obtain nitrogen-doped chromium carbide.

[0047] Example 1

[0048] This example provides a preparation method of a high-strength hardware stamping die, including the following steps:

[0049] Step S1: By weight, 30 parts of tungsten carbide and 50 parts of vinyl polycarbosilane were mixed evenly and ball milled for 60h, and then under the protection of nitrogen gas, the temperature was raised to 1200°C and kept warm for 60min, and then cooled to room temperature to obtain a porous material; 30 parts of the porous material and 8 parts of boron quantum dots were mixed, and under the protection of helium gas, the temperature was raised to 1700°C and kept warm for 1h, and then cooled to room temperature at a rate of 10°C / min, and pulverized to obtain boron-containing tungsten carbide;

[0050] Step S2: Mix 60 parts of the boron-containing tungsten carbide, 40 parts of modified cobalt powder, 6 parts of nitrogen-doped chromium carbide, and 4 parts of carbon black evenly by weight, and then perform ball milling (first add 10 parts of paraffin and pre-mill for 20 min, then add 500 parts of absolute ethanol and ball mill at 40 r / min for 24 h) to obtain a slurry;

[0051] Step S3: Spray-dry the slurry, then press it into a green compact, and perform dewaxing and sintering treatment on the green compact to obtain a sintered compact;

[0052] The conditions of the dewaxing and sintering treatment include: introducing high-pressure argon gas for pressurization at a temperature of 1340 °C, with a pressure of 10 bar, a sintering time of 30 min, and then cooling and taking out of the furnace;

[0053] Step S4: Quench and then perform low-temperature tempering treatment on the sintered compact in sequence to obtain a high-strength hardware stamping die;

[0054] The conditions of the quenching treatment include: heating in a vacuum environment at a heating rate of 4 °C / min to 800 °C, holding for 20 min, then heating at a heating rate of 5 °C / min to 1100 °C, holding for 30 min, and finally filling with 3 bar of argon gas and quickly cooling to room temperature;

[0055] The conditions of the low-temperature tempering treatment include: heating at a heating rate of 1 °C / min to 200 °C, holding for 4 h, and naturally cooling to room temperature.

[0056] Example 2

[0057] This example provides a method for preparing a high-strength hardware stamping die, including the following steps:

[0058] Step S1: Mix 20 parts of tungsten carbide and 40 parts of vinyl polycarbosilane evenly by weight, then ball mill for 50 h, and then under the protection of nitrogen gas, heat up to 1000 °C and hold for 90 min, and cool to room temperature to obtain a porous material; mix 20 parts of the porous material and 6 parts of boron quantum dots, under the protection of helium gas, heat up to 1600 °C and hold for 3 h, cool to room temperature at a rate of 6 °C / min, and pulverize to obtain boron-containing tungsten carbide;

[0059] Step S2: Mix 50 parts of the boron-containing tungsten carbide, 30 parts of modified cobalt powder, 4 parts of nitrogen-doped chromium carbide, and 2 parts of carbon black evenly by weight, and then perform ball milling (first add 6 parts of paraffin and pre-mill for 10 min, then add 400 parts of absolute ethanol and ball mill at 38 r / min for 28 h) to obtain a slurry;

[0060] Step S3: Spray-dry the slurry, then press it into a green compact, and perform dewaxing and sintering treatment on the green compact to obtain a sintered compact;

[0061] The conditions for the dewaxing and sintering treatment include: introducing high-pressure argon gas under the condition of a temperature of 1320 °C for pressurization, with a pressure of 8 bar, a sintering time of 40 min, and then cooling and taking out of the furnace after cooling;

[0062] Step S4: Quench and then perform low-temperature tempering on the sintered blank in sequence to obtain a high-strength metal stamping die;

[0063] The conditions for the quenching treatment include: heating in a vacuum environment at a heating rate of 4 °C / min to 760 °C, holding for 30 min, then heating at a heating rate of 5 °C / min to 1000 °C, holding for 40 min, and finally filling with 1 bar of argon gas and rapidly cooling to room temperature;

[0064] The conditions for the low-temperature tempering treatment include: heating at a heating rate of 1 °C / min to 180 °C, holding for 6 h, and then naturally cooling to room temperature.

[0065] Example 3

[0066] This example provides a preparation method for a high-strength metal stamping die, including the following steps:

[0067] Step S1: By weight, mix 25 parts of tungsten carbide and 45 parts of vinyl polycarbosilane evenly, then ball mill for 55 h, and then under the protection of nitrogen gas, heat up to 1100 °C and hold for 80 min, and cool to room temperature to obtain a porous material; mix 25 parts of the porous material and 7 parts of boron quantum dots, under the protection of helium gas, heat up to 1650 °C and hold for 2 h, cool to room temperature at a rate of 8 °C / min, and pulverize to obtain boron-containing tungsten carbide;

[0068] Step S2: By weight, mix 55 parts of the boron-containing tungsten carbide, 35 parts of modified cobalt powder, 5 parts of nitrogen-doped chromium carbide, and 3 parts of carbon black evenly, and then perform ball milling treatment (first add 8 parts of paraffin and pre-mill for 15 min, then add 450 parts of absolute ethanol and ball mill for 26 h under the condition of 39 r / min) to obtain a slurry;

[0069] Step S3: Spray-dry the slurry, then press and mold to obtain a green compact, and perform dewaxing and sintering treatment on the green compact to obtain a sintered blank;

[0070] The conditions for the dewaxing and sintering treatment include: introducing high-pressure argon gas under the condition of a temperature of 1330 °C for pressurization, with a pressure of 9 bar, a sintering time of 35 min, and then cooling and taking out of the furnace after cooling;

[0071] Step S4: Quench and then perform low-temperature tempering on the sintered blank in sequence to obtain a high-strength metal stamping die;

[0072] The conditions for the quenching treatment include: heating to 780°C at a heating rate of 4°C / min in a vacuum environment, holding for 25 min, then heating to 1050°C at a heating rate of 5°C / min, holding for 35 min, and finally filling with 2 bar of argon gas and rapidly cooling to room temperature;

[0073] The conditions for the low-temperature tempering treatment include: heating to 190°C at a heating rate of 1°C / min, holding for 5 h, and naturally cooling to room temperature.

[0074] Comparative Example 1

[0075] This comparative example provides a method for preparing a metal stamping die, which is different from Example 1 in that commercially available tungsten carbide is used to replace boron-containing tungsten carbide, commercially available cobalt powder is used to replace modified cobalt powder, and commercially available chromium carbide is used to replace nitrogen-doped chromium carbide.

[0076] Comparative Example 2

[0077] This comparative example provides a method for preparing a metal stamping die, which is different from Comparative Example 1 in that boron-containing tungsten carbide is used to replace commercially available tungsten carbide.

[0078] Comparative Example 3

[0079] This comparative example provides a method for preparing a metal stamping die, which is different from Comparative Example 1 in that modified cobalt powder is used to replace commercially available cobalt powder.

[0080] Comparative Example 4

[0081] This comparative example provides a method for preparing a metal stamping die, which is different from Comparative Example 1 in that nitrogen-doped chromium carbide is used to replace commercially available chromium carbide.

[0082] Comparative Example 5

[0083] This comparative example provides a method for preparing a metal stamping die, which is different from Example 1 in that commercially available tungsten carbide is used to replace boron-containing tungsten carbide.

[0084] Comparative Example 6

[0085] This comparative example provides a method for preparing a metal stamping die, which is different from Example 1 in that commercially available cobalt powder is used to replace modified cobalt powder.

[0086] Comparative Example 7

[0087] This comparative example provides a method for preparing a metal stamping die, which is different from Example 1 in that commercially available chromium carbide is used to replace nitrogen-doped chromium carbide.

[0088] The performance of the metal stamping dies provided in the above examples and comparative examples was tested. The specific test method is as follows:

[0089] (1) Rockwell hardness test

[0090] The Rockwell hardness test is carried out according to the requirements of "GB / T 230.1-2018 Metallic materials - Rockwell hardness test - Part 1: Test method".

[0091] (2) Transverse rupture strength test

[0092] The transverse rupture strength test is carried out according to the requirements of "GB / T 3851-2015 Cemented carbides - Determination of transverse rupture strength".

[0093] (3) Fracture toughness test

[0094] The fracture toughness test is carried out according to the requirements of "GB / T 33819-2017 Cemented carbides - Bend toughness test".

[0095] The above performance test data are shown in Table 1.

[0096] Table 1 Performance test results

[0097]

[0098] As can be seen from the above, in the present invention, by selecting boron-containing tungsten carbide as the main component and using modified cobalt powder and nitrogen-doped chromium carbide in combination, high-strength hardware stamping dies (Examples 1 to 3) are prepared, with a Rockwell hardness (HRA) of 84.6 - 85.1, a transverse rupture strength of 2608 - 2623 MPa, and a fracture toughness of 8.8 - 9.1 MPa·m 1 / 2 .

[0099] Compared with Example 1, when using commercially available tungsten carbide to replace boron-containing tungsten carbide, commercially available cobalt powder to replace modified cobalt powder, and commercially available chromium carbide to replace nitrogen-doped chromium carbide, the Rockwell hardness decreases, the transverse rupture strength decreases, and the fracture toughness deteriorates (Comparative Example 1); compared with Comparative Example 1, when using boron-containing tungsten carbide to replace commercially available tungsten carbide, the Rockwell hardness increases (Comparative Example 2); compared with Comparative Example 1, when using modified cobalt powder to replace commercially available cobalt powder, the transverse rupture strength increases (Comparative Example 3); compared with Comparative Example 1, when using nitrogen-doped chromium carbide to replace commercially available chromium carbide, the fracture toughness improves (Comparative Example 4); compared with Example 1, when using commercially available tungsten carbide to replace boron-containing tungsten carbide, the Rockwell hardness decreases, the transverse rupture strength decreases, and the fracture toughness deteriorates (Comparative Example 5); compared with Example 1, when using commercially available cobalt powder to replace modified cobalt powder, the Rockwell hardness decreases, the transverse rupture strength decreases, and the fracture toughness deteriorates (Comparative Example 6); compared with Example 1, when using commercially available chromium carbide to replace nitrogen-doped chromium carbide, the Rockwell hardness decreases, the transverse rupture strength decreases, and the fracture toughness deteriorates (Comparative Example 7).

[0100] In summary, the present invention selects tungsten boride carbide as the main component of the mold, and combines it with the co-use of modified cobalt powder and nitrogen-doped chromium carbide to prepare a high-strength metal stamping mold. Through the synergistic effect of each component, the Rockwell hardness and transverse rupture strength of the mold are effectively improved, and good fracture toughness is obtained at the same time.

Claims

1. A preparation method of a high-strength hardware stamping die, characterized in that It includes the following steps: Step S1: By weight, mix 20 - 30 parts of tungsten carbide and 40 - 50 parts of vinyl polycarbosilane evenly, then ball mill for 50 - 60 h. Then, under the protection of nitrogen gas, heat up to 1000 - 1200 °C and keep warm for 60 - 90 min, and cool to room temperature to obtain a porous material; mix 20 - 30 parts of the porous material and 6 - 8 parts of boron quantum dots, under the protection of helium gas, heat up to 1600 - 1700 °C and keep warm for 1 - 3 h, cool to room temperature at a rate of 6 - 10 °C / min, and pulverize to obtain boron-containing tungsten carbide; Step S2: By weight, mix 50 - 60 parts of the boron-containing tungsten carbide, 30 - 40 parts of cobalt powder, 4 - 6 parts of chromium carbide, and 2 - 4 parts of carbon black evenly, and then carry out ball milling treatment to obtain a slurry; Step S3: Spray dry the slurry, then press it into a green compact, and carry out dewaxing sintering treatment on the green compact to obtain a sintered compact; Step S4: Carry out quenching treatment and low-temperature tempering treatment on the sintered compact in sequence to obtain a high-strength metal stamping die.

2. The preparation method of a high-strength metal stamping die according to claim 1, characterized in that, The preparation method of the boron quantum dots includes: By weight, add 2 - 4 parts of boron powder into 80 - 100 parts of isopropanol and mix evenly, then add 4 - 6 parts of boric acid and 6 - 8 parts of hydrogen peroxide, carry out ultrasonic crushing at a power of 600 - 640 W for 120 - 160 min. After the ultrasonic crushing ends, add 3 - 5 parts of sodium borohydride and stir for 22 - 24 h, centrifuge to obtain the supernatant, add 2 - 4 parts of hydrazine hydrate to the supernatant and carry out ultrasonic oscillation for 20 - 30 min, and freeze-dry to obtain the boron quantum dots.

3. The preparation method of a high-strength hardware stamping die according to claim 1, characterized in that, The cobalt powder is modified cobalt powder; The preparation method of the modified cobalt powder includes: By weight, add 20 - 30 parts of cobalt powder and 6 - 10 parts of graphene oxide into 90 - 100 parts of deionized water, ball mill and mix evenly to obtain a mixed solution, freeze-dry the mixed solution to obtain a composite powder, and then carry out heat treatment on the composite powder under the protection of hydrogen gas atmosphere (temperature is 520 - 540 °C, time is 2 - 4 h) to obtain the modified cobalt powder.

4. The preparation method of a high-strength hardware stamping die according to claim 1, characterized in that, The chromium carbide is nitrogen-doped chromium carbide; The preparation method of the nitrogen-doped chromium carbide includes: By weight, add 8 - 12 parts of chromium nitrate, 1 - 3 parts of glycine, and 10 - 14 parts of glucose into 40 - 50 parts of deionized water and mix evenly, then heat and stir at 140 - 160 °C for 40 - 60 min, and dry to obtain a precursor powder; mix 10 - 16 parts of the precursor powder and 6 - 8 parts of urea and place them in a tubular furnace, carry out high-temperature treatment under the protection of nitrogen atmosphere, and after the high-temperature treatment is completed, cool to room temperature, wash, and dry to obtain the nitrogen-doped chromium carbide.

5. The preparation method of a high-strength hardware stamping die according to claim 4, characterized in that, The conditions of the high-temperature treatment include: temperature is 760 - 780 °C, time is 2 - 4 h.

6. The preparation method of a high-strength metal stamping die according to claim 1, characterized in that, The conditions of the ball milling treatment include: first add 6 - 10 parts of paraffin and pre-mill for 10 - 20 min, then add 400 - 500 parts of absolute ethanol and ball mill at 38 - 40 r / min for 24 - 28 h.

7. The preparation method of a high-strength hardware stamping die according to claim 1, characterized in that, The conditions for the dewaxing and sintering treatment include: introducing high-pressure argon gas for pressurization at a temperature of 1320 - 1340 °C, with a pressure of 8 - 10 bar, a sintering time of 30 - 40 min, and then taking out of the furnace after cooling.

8. The preparation method of a high-strength hardware stamping die according to claim 1, characterized in that, The conditions for the quenching treatment include: heating to 760 - 800 °C at a heating rate of 4 °C / min in a vacuum environment, holding for 20 - 30 min, then heating to 1000 - 1100 °C at a heating rate of 5 °C / min, holding for 30 - 40 min, and finally filling with 1 - 3 bar argon gas and quickly cooling to room temperature.

9. The preparation method of a high-strength metal stamping die according to claim 1, wherein, The conditions for the low-temperature tempering treatment include: heating to 180 - 200 °C at a heating rate of 1 °C / min, holding for 4 - 6 h, and naturally cooling to room temperature.

10. A high-strength metal stamping die, characterized in that, Prepared by the method according to any one of claims 1 - 9.